Pulse cyclophosphamide induction treatment in Thai children with diffuse proliferative lupus nephritis - Opastirakul S. (2014)
Aim: To report the effectiveness of pulse cyclophosphamide induction therapy and to identify predictors for unresponsiveness to treatment in Thai children. Methods: Children with biopsy-proven diffuse proliferative lupus nephritis admitted to Chiang Mai University hospital between 2001 and 2006 were retrospectively studied. Patients received a test dose of 750 mg/m 2 at the first month followed by six cycles of monthly cyclophosphamide (IVCY) at a dose of 1 g/m 2 (maximum 1 g) as induction therapy. Responsiveness to treatment, defined as urinary protein to creatinine ratio of less than 0.3 with normalization of C3 level and clinical remission, was assessed at the end of the induction period. Gender, age at onset, duration of disease before treatment, hypertension, clinical nephrotic syndrome, amount of proteinuria, serum creatinine, creatinine clearance, serum C3 level and crescentic formation were compared between responsive and nonresponsive groups. Maintenance therapy with quarterly pulse IVCY or Azathioprine or Mycophenolate mofetil was given for 18-24 months after remission. Results: Twenty nine patients with a mean age of 10.3 ± 2.6 years were studied. Hypertension, microscopic haematuria and nephrotic-range proteinuria were seen in 66%, 86% and 60% of the patients, respectively. Forty-one per cent of biopsies showed cellular or fibrocellular crescents. Twenty patients (69%) achieved remission at the end of induction therapy. There were no significant differences in all parameters studied between responsive and nonresponsive groups. The relapse rate after maintenance therapy was 58.8%. Conclusion: Our results show that pulse cyclophosphamide is an effective regimen for induction therapy in children with diffuse proliferative glomerulonephritis. No definite predictor for unresponsiveness was detected in this study. Opastirakul et al. reported the short-term efficacy of intravenous pulse cyclophosphamide (IVCY) as an induction therapy in children with diffuse proliferative lupus nephritis (LN). Although they could not find any predictive factors for unresponsiveness, they concluded that the IVCY was an effective therapy for children with severe diffuse proliferative LN. © 2011 Asian Pacific Society of Nephrology.